2020
DOI: 10.1016/j.esxm.2020.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and Optimal Therapeutic Dosage of Clomipramine for Premature Ejaculation: A Systematic Review and Meta-Analysis

Abstract: Introduction Clomipramine is effective in treating premature ejaculation, a common form of male sexual dysfunction that affects individual's mental health and quality of life, but its optimal dosage remains controversial. Aim In this systematic review and meta-analysis, we aimed to evaluate the efficacy, safety, and optimal dose of clomipramine for treating premature ejaculation among men. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Of all, several systematic reviews and meta-analyses of drug treatment studies showed that, despite methodological problems in most studies, daily SSRIs are significantly effective for PE [3,176,182]. Paroxetine was found to be superior to fluoxetine, clomipramine, and sertraline [3,[183][184][185][186]. Likewise, tramadol, a mild opioid receptor agonist that also promotes reuptake inhibition of serotonin and noradrenaline, has been demonstrated to be effective as an off-label on-demand oral therapy in men with a history of lifelong PE [3,187,188].…”
Section: Weakmentioning
confidence: 99%
“…Of all, several systematic reviews and meta-analyses of drug treatment studies showed that, despite methodological problems in most studies, daily SSRIs are significantly effective for PE [3,176,182]. Paroxetine was found to be superior to fluoxetine, clomipramine, and sertraline [3,[183][184][185][186]. Likewise, tramadol, a mild opioid receptor agonist that also promotes reuptake inhibition of serotonin and noradrenaline, has been demonstrated to be effective as an off-label on-demand oral therapy in men with a history of lifelong PE [3,187,188].…”
Section: Weakmentioning
confidence: 99%
“…The types of eligible studies included cross-sectional, case-control, and cohort studies. Two experienced reviewers (S.-H. Ma and P.-C. Wu) independently performed the literature search, data extraction, and quality assessment [9, 17, 18]. Any disagreement was resolved by consensus among the reviewers or referred to a third reviewer (Y.-X.…”
Section: Methodsmentioning
confidence: 99%
“…Our clinical findings and literature analysis suggest that not all patients respond to dapoxetine and experience varying degrees of withdrawal (Mondaini et al, 2013). Sertraline, paroxetine, citalopram and clomipramine all can prevent central serotonin uptake and are used to treat premature ejaculation (Arafa et al, 2006; Rezakhaniha et al, 2014; Salonia et al, 2009; Wu et al, 2021). Fluoxetine is a serotonin reuptake inhibitor that induces delayed ejaculation by reducing vasoconstriction while simultaneously increasing central serotonin levels (Giuliano, 2007).…”
Section: Introductionmentioning
confidence: 99%